2005
DOI: 10.1038/sj.ijir.3901376
|View full text |Cite
|
Sign up to set email alerts
|

Use of a validated quality of life questionnaire to assess sexual function following laparoscopic radical prostatectomy

Abstract: Wide variations exist in the methods for evaluating potency following radical prostatectomy. We describe our technique of laparoscopic radical prostatectomy (LRP), present our methods for assessing the return of potency following LRP, and discuss the relevant literature. Sexual function was assessed pre-and postoperatively using the Expanded Prostate Cancer Index Composite questionnaire (EPIC). Sexual function subscale scores (SFSS) were reported as a percentage of preoperative baseline sexual function. The EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Many more studies have used the EPIC to assess ED in prostate cancer patients. For example, outcomes after laparoscopic, 22 robot-assisted, 10 retropubic, 23 and perineal 24 radical prostatectomy have been reported based on the EPIC instrument. Similarly, the EPIC has been used to follow patients after external-beam radiotherapy or brachytherapy for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many more studies have used the EPIC to assess ED in prostate cancer patients. For example, outcomes after laparoscopic, 22 robot-assisted, 10 retropubic, 23 and perineal 24 radical prostatectomy have been reported based on the EPIC instrument. Similarly, the EPIC has been used to follow patients after external-beam radiotherapy or brachytherapy for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(16) EPIC has now been used in several studies to evaluate patient reported health-related QoL outcomes in the management of prostate cancer (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al [30] investigated the impact of nerve sparing during LRP on the sexual function of men using the EPIC questionnaire. The sexual function subscale score (SFSS) was reported as a percentage of baseline preoperative sexual function.…”
Section: Sexual Functionmentioning
confidence: 99%